Political Preferences for Redistribution in Sweden - Spencer Bastani; Jacob Lundberg (Center for Economic Studies and ifo Institute (CESifo), 2016)
We examine preferences for redistribution inherent in Swedish tax policy 1971–2012 using the inverse optimal tax approach. The income distribution is carefully characterized with the help of administrative register data and we employ behavioral elasticities reflecting the perceived distortionary effects of taxation. The revealed social welfare weights are high for non-workers, small for low-income earners, and hump-shaped around the median. At the top, they are always negative, especially so during the high-tax years of the 1970s and 80s. The weights on non-workers increased sharply in the 1970s fell drastically in the late 80s/early 90s, and have since then increased.
Keywords: D63; H21; 330; redistribution; social welfare weights; optimal taxation; inverse optimal taxation; social preferences